Research of characteristics of working cycle of high-speed diesel engine operating on biofuels RME–E and D–RME–E. Part 1. Indicators of fuel injection system and indicative process - Lebedevas, Sergejus; Lebedeva, Galina; Gudaitytė, Ingrida (Transport, 2013)
The article provides the results of an analyses of the characteristics of fuel injection system as well as the processes indicated in diesel engines 1A41 and F2L511, transferred from working with mineral diesel to working with rapeseed methyl ester–ethanol (RME–E) and mineral diesel fuel–rapeseed methyl ester–ethanol (D–RME–E). In biofuel, ethanol takes a part of 10÷40%. It was found that the E part in the fuel causes a lag of fuel injection of 2÷6 CA (greater values of fuel injection lag are common for partial engine loads and greater amount of E in fuel) that does not occur with mineral diesel fuel or RME. The analysis shows how a lag of fuel ignition limits the dynamic parameters (P max, (d p/d ϕ)max) of the cycle and specific emission of nitric oxides (eNOx) in exhaust gas. It is possible to convert diesel engines, operating on D to ethanol-containing biofuels without adjusting the fuel injection system parameters. At the same time, it is necessary to increase residual pressure in high-pressure fuel line of diesel engines with fuel injection pressure of 60÷70 MPa. First Published Online: 16 Jul 2013